E-Business State of the Art of ICT Based Challenges and Solutions - Perakovic, Dragan (IntechOpen, 2017)
In this book, authors provide latest results of scientific research projects within the area of e-business: Challenges of Information and Communication Technology Usage in E-business Systems; A Proposal for Brand Analysis with Opinion Mining; Customers Online Interaction Experiences with Fashion Brands: E-information and E-buying; Payment System's Determination by Universal Financial Industry Message Scheme According to Single Euro Payment Area; and CSFs for SMEs in Measuring E-commerce Success.